Loathing Lincoln : An American Tradition from the Civil War to the Present - Barr, John McKee, 1962- (Book collections on Project MUSE., 2014)
"An analysis of Lincoln in historical memory and an examination of how his critics--on both the right and the left--have frequently reflected the anxiety and discontent Americans felt about their lives."--Publisher description.